Antiproliferative and cell cycle arrest potentials of 3-O-acetyl-11-keto-β-boswellic acid against MCF-7 cells in vitro - Saja A. Ahmed; Ahmed F. Al-Shanon; Ali Z. Al-Saffar; Alene Tawang; Jameel R. Al-Obaidi (Journal of Genetic Engineering and Biotechnology, 2023)
Abstract Introduction Cancer is a major issue in medical science with increasing death cases every year worldwide. Therefore, searching for alternatives and nonorthodox methods of treatments with high efficiency, selectivity and less toxicity is the main goal in fighting cancer. Acetyl-11-keto-β-boswellic acid (AKBA), is a derivative pentacyclic triterpenoid that exhibited various biological activities with potential anti-tumoral agents. In this research, AKBA was utilized to examine the potential cytotoxic activity against MCF-7 cells in vitro and monitor the cellular and morphological changes with a prospective impact on apoptosis induction. Methods The cytotoxic activity of AKBA was measured by 3(4,5dimethylthiazole- 2-yl)-2,5 diphyneltetrazolium bromide (MTT) assay. A dose-dependent inhibition in MCF-7 cell viability was detected. The clonogenicity of MCF-7 cells was significantly suppressed by AKBA increment in comparison with untreated cells. Result Morphologically, exposure of MCF-7 cells to high AKBA concentrations caused changes in cell nuclear morphology which was indicated by increasing in nuclear size and cell permeability intensity. The mitochondrial membrane potential (ΔΨm) was reduced by increasing AKBA concentration with a significant release of cytochrome c. Acridine orange/ethidium bromide dual staining experiment confirmed that MCF-7 cells treated with AKBA (IC50 concentration) displayed a late stage of apoptosis indicated by intense and bright reddish colour. Conclusion A significant increase in reactive oxygen species formation was observed. Caspase 8 and caspase 9 activities were estimated and AKBA activated the production of caspase 8 and caspase 9 in a dose-dependent pattern. Finally, the cell phase distribution analysis was conducted, and flow cytometric analysis showed that AKBA at 200 μg mL-1 significantly arrest MCF-7 cells at the G1 phase and triggered apoptosis.